2016
DOI: 10.1002/2015ja022133
|View full text |Cite
|
Sign up to set email alerts
|

The response of equatorial electrojet, vertical plasma drift, and thermospheric zonal wind to enhanced solar wind input

Abstract: In this study we used observations from the CHAMP and ROCSAT‐1 satellites to investigate the solar wind effects on the equatorial electrojet (EEJ), vertical plasma drift, and thermospheric zonal wind. We show that an abrupt increase in solar wind input has a significant effect on the low‐latitude ionosphere‐thermosphere system, which can last for more than 24 h. The disturbance EEJ and zonal wind are mainly westward for all local times and show most prominent responses during 07–12 and 00–06 magnetic local tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 53 publications
6
47
0
Order By: Relevance
“…Sahai et al () reported that the strong positive storm occurred during the main and recovery phase of the storm, and the density enhancement above the equatorial anomaly on the night of recovery phase was much stronger than that on the night of main phase. The different response to the storm during the recovery phase in different longitude sectors means that the storm effects on the ionosphere depend on the longitudes (Xu et al, ), especially during the recovery phase when the disturbance wind dynamo dominant the equatorial and low latitudes (Xiong et al, ). Furthermore, it can be noticed that the EIA density asymmetry and location asymmetry shown in Figures and increased with respect to the earlier several days, which means that the existence of the neutral wind and the effect of the neutral wind was remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…Sahai et al () reported that the strong positive storm occurred during the main and recovery phase of the storm, and the density enhancement above the equatorial anomaly on the night of recovery phase was much stronger than that on the night of main phase. The different response to the storm during the recovery phase in different longitude sectors means that the storm effects on the ionosphere depend on the longitudes (Xu et al, ), especially during the recovery phase when the disturbance wind dynamo dominant the equatorial and low latitudes (Xiong et al, ). Furthermore, it can be noticed that the EIA density asymmetry and location asymmetry shown in Figures and increased with respect to the earlier several days, which means that the existence of the neutral wind and the effect of the neutral wind was remarkable.…”
Section: Discussionmentioning
confidence: 99%
“…This is the time they claim that it takes for the disturbance dynamo to affect the low latitudes. In the recent study Xiong et al [] have confirmed by means of a superposed epoch analysis that about 3 h after a sudden increase of solar wind input into the magnetosphere‐ionosphere system (after the PPEF effect has ceased) westward winds and downward plasma drifts dominate for many hours in the postsunset sector. Both these forces stabilize the ionosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, we expect a delayed and smoothed response of ionospheric plasma density to changes of the IEF. This retarded reaction has been taken into account by using a similar approach as utilized in previous studies [e.g., Richmond et al , ; Xiong et al , ]: Em(),tτ=t1tEm()te()tttrue/τdtt1te()tttrue/τdt where Em is treated as a continuous function of time t ′, t 1 is chosen 3 h before the actual epoch, and τ is the e ‐folding time of the weighting function in the integrands, with a value τ = 0.5 h. These parameters have been found to be suitable for ionospheric studies like Xiong et al [, and references therein]. In Figure d Em is presented, as calculated by equation , by a blue line, and the red line shows the time‐integrated E m obtained by equation .…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also reported that the semidiurnal tide SW3 causes largest EEJ amplitudes from October to December. Recently Xiong et al [2016] examined the longitudinal wave patterns of the EEJ during quiet and disturbed periods. They found that even during magnetically disturbed periods (Kp > 3) the WN4 pattern of the EEJ can still be clearly recognized (especially during September equinox), but with lower amplitudes when compared to quiet periods.…”
Section: Introductionmentioning
confidence: 99%